Factors associated with chronic back pain in adults in Brazil - Malta, Deborah Carvalho; Oliveira, Max Moura de; Andrade, Silvânia Suely Caribé de Araújo; Caiaffa, Waleska Teixeira; Souza, Maria de Fatima Marinho de; Bernal, Regina Tomie Ivata (Revista de Saúde Pública, 2017)
OBJECTIVE To identify associations of chronic back pain with sociodemographic characteristics, lifestyles, body mass index, self-reported chronic diseases and health assessment, according to sex. METHODS We analyzed data from the 2013 National Health Survey, estimated the prevalence and their respective 95% confidence intervals (95%CI) of chronic back pain, according to selected variables and performed adjustment by age and education. RESULTS 18.5% of the Brazilian population reported chronic back pain, 15.5% (95%CI 14.7–16.4) of them being men and 21.1% (95%CI 20.2–22.0) being women. The characteristics that remained associated and statistically significant (p < 0.05) after adjustment, in men, were: age group, higher in men with 65 years or older (ORa = 6.06); low education level; living in rural area; history of smoking, high salt intake, increase in the time of heavy physical activity at work and at home; being overweight (ORa = 1.18) or obese (ORa = 1.26); diagnostic of hypertension (ORa = 1.42), high cholesterol (ORa = 1.60); and worse health assessment in comparison with very good (good [ORa = 1.48]; regular [ORa = 3.22]; poor [ORa = 5.00], very poor [ORa = 8.60]). Among women, they were: increase with age, higher among women with 55-64 years (ORa = 3.64); low education level; history of smoking, regular candy consumption, high salt intake, heavy physical activity at work and at home and increase in the time of these activities; being overweight (ORa = 1.23) or obese (ORa = 1.32); diagnosis of hypertension (ORa = 1.50), high cholesterol (ORa = 1.84); and worse health assessment than very good (good [ORa = 1.43]; regular [ORa = 3.16]; poor [ORa = 5.44], very poor [ORa = 8.19]). CONCLUSIONS Our findings point out differences by sex and contribute to the knowledge of the panorama of chronic back pain, which, besides affecting individuals, generate negative socioeconomic impacts, by causing work-related disabilities and hindering everyday activities.